Employee behavior in organizations: On the current state of research - Lutz von Rosenstiel (Management Revue, 2011)
The article gives an overview about scientific research on individual behavior in organizations. A number of reasons are discussed why it is difficult to obtain a coherent body of knowledge about this topic, some of them meta-theoretical and methodological, others political, organizational and ideological, e.g. the existence of different schools of psychology, one-sided and interest-laden views, the dominance of survey methodology, measurement problems, the submission of researchers to dominant styles of publishing. The article further reports on main insights about the effects of stable and variable personal traits, and of situational conditions on employee behavior and about practical consequences. The conclusion is that there is a lot of well-founded knowledge, especially about the aptitudes of employees, but on the other hand one finds remarkable ignorance on behaviour which has no direct relation to performance and on the impacts of specific work and organizational conditions.
Keywords: J23; J24; J28; M12; M54; 650; organizational behavior; organizational psychology; performance; leadership; personal traits